Climate Change and Legal Responsibility: Challenges and Solutions from the Perspective of Environmental Jurisprudence - Aldarmaki, Muna Ateeq Rubayea (Journal of Islamic Sciences, 2024)
The study addressed climate change and the legal responsibility resulting from it. Climate change is one of the most important challenges facing humanity in the current era, as it causes extreme climate changes, such as rising temperatures, changing rainfall patterns, and rising sea levels, which have devastating effects on the Environment and human societies. In the context of the legitimate responsibility resulting from climate change, states have a fundamental role in leading international efforts to combat climate change.It was talked about that confronting climate change requires joint efforts from all people, as no individual or organization can achieve this alone. Therefore, adhering to our legitimate responsibility in confronting climate change is a moral and necessary duty to preserve the planet for future generations.This study aimed to clarify the role of legitimate responsibility resulting from climate change and to identify possible solutions to limit climate change from the standpoint of legitimate policy. The study also concluded that Islam has the lead in protecting and preserving the environment before establishing governments and international institutions and previous and subsequent laws as the most important result. The study recommends conducting more studies concerned with climate change and how to confront it, especially from a legal perspective.
Keywords: Climate change; international responsibility; Environmental jurisprudence; Sharia policy